Obtaining and characterization of nanostructured coatings of zirconia-alumina-ceria by thermal spray flame. (November 2019) - Rodríguez, L F; Ferrer, M; Peña, G
Abstract: Zirconia, alumina and ceria powders were agglomerated, by granulator disk, to be used as raw material in the manufacture of coatings on red clay substrates by flame spray. Three mixtures of different compositions were made to determine which of them produces the most homogeneous and best bonded coatings. Likewise, the phase transformations that occur in the thermal spraying process were evaluated. The morphology and microstructure of the powders and coatings were determined by scanning electron microscopy and X-ray diffraction, respectively. Bimodal coatings were obtained, preserving the nanometric structure of the powders, homogeneous, low porosity and good adhesion.